Turysta w poszukiwaniu domu: tożsamość ponowoczesna w „Encyklopedii duszy rosyjskiej” Wiktora Jerofiejewa - Stryjakowska, Anna (Studia Rossica Posnaniensia, 2015)
This article investigates the issue of postmodern identity in Victor Erofeev’s Encyclopaedia of the Russian Soul with reference to Zygmunt Bauman’s thoughts on liquid modernity. The narrator of the novel can be seen as a tourist in search of a home as his attempts to define his individual identity are deeply connected with the need to find the Russian Idea.